A study of correlation of pulmonary function test in patients with metabolic syndrome with different components of metabolic syndrome - S., Prabhu; Karbari, Sudha (International Journal of Advances in Medicine, 2022)
Background: The increasing incidence of metabolic syndrome has been on the rise especially in urban population and leading to increased risk of cardiovascular disease (CVD) and diabetes mellitus. It has been associated with impairment of pulmonary functions. However, there is limited data regarding the association with individual components of metabolic syndrome and overall effect on components of pulmonary functions. Methods: This is a cross sectional study consisting of 50 subjects with metabolic syndrome. All the subjects underwent pulmonary function tests and the association between different components of metabolic syndrome and pulmonary function were examined using unpaired t-test and Pearson’s partial correlation coefficient. This data was analysed by using statistical package for the social sciences (SPSS) version 12.0. Results: In females, moderate negative significant correlation was seen between forced vital capacity (FVC) and systolic blood pressure (SBP), diastolic blood pressure (DBP), fasting blood sugar (FBS), triglyceride (TG), waist circumference (WC) and body mass index (BMI) whereas positive weak non-significant correlation was seen between FVC and high density lipoprotein cholesterol (HDLC), while no such relation was found with forced expiratory volume in one second (FEV1). In males, negative, moderate significant correlation was seen between FVC and FBS whereas strong, positive, significant correlation was seen between FVC and WC; between FVC and BMI. Negative, moderate, significant correlation was seen between FEV1 and WC; between FEV1 and BMI. Conclusions: Our study concluded that there was a significant impact of FBS and WC on decreasing FVC on both genders with minimally significant impact of other components of metabolic syndrome on FVC with no effect on FEV1 hence indicating a restrictive pattern of pulmonary function derangement. Hence, further studies with larger sample size is needed to confirm whether there are direct or indirect mechanisms through which insulin resistance could affect pulmonary function.